Generalized Higher Derivations on Î“M-Modules - Mahmood, Auday Hekmat; Nayef, Mahdi Saleh; Salih, Salah Mehdi (Iraqi Journal of Science, 2020)
The concepts of generalized higher derivations, Jordan generalized higher derivations, and Jordan generalized triple higher derivations on Î“-ring M into Î“M-modules X are presented. We prove that every Jordan generalized higher derivation of Î“-ring M into 2-torsion free Î“M-module X, such that aÎ±bÎ²c=aÎ²bÎ±c, for all a, b, c ïƒŽM and Î±,Î²ïƒŽÎ“, is Jordan generalized triple higher derivation of M into X.